Cryptococcal Meningitis Presenting as a Complication in HIV-infected Children: A Case Series From Sub-Saharan Africa. Issue 9 (September 2016) - Nyazika, Tinashe K.; Masanganise, Faith; Hagen, Ferry; Bwakura-Dangarembizi, Mutsawashe F.; Ticklay, Ismail M. H.; Robertson, Valerie J.
Abstract : Abstract: Cryptococcal meningitis is a leading infectious disease worldwide as a result of the high burden of HIV and AIDS, although its cumulative incidence is very low in children compared with that in adults. Very few studies involving the disease in children have been reported including sub-Saharan Africa, with the highest prevalence of HIV-infected children in the world. We summarize 5 cases of children diagnosed with cryptococcal meningitis at a tertiary hospital in Harare, Zimbabwe, between October 1, 2013, and September 30, 2014.